Hegyidomtan. Sopron 1950 és Hegyidomtan. I–II. Bp. 1951. - Irmédi-Molnár László (Fond 165 Irmédi-Molnár László)
Fond 165 Irmédi-Molnár László > Irmédi-Molnár László iratai. > Irmédi-Molnár László művei és anyaggyűjtései kül. témákhoz > Domborzattan. Hegyábrázolás.